1999
DOI: 10.1046/j.1365-2605.1999.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in testicular transferrin concentrations measured by enzyme immunoassay after FSH administration to beagle dogs

Abstract: A sensitive enzyme immunoassay (EIA) was developed for transferrin (Tf) in the canine testis, as an effective marker of Sertoli cell function. Tf was purified from male dog serum by DEAE-Affi-Gel Blue chromatography and gel filtration. Rabbits were immunized with the Tf, and anti-dog Tf antibody was purified from the rabbit serum by affinity chromatography as primary antibody for EIA. Peroxidase-conjugated goat anti-dog Tf antibody was used as the secondary antibody for microtitre plate double-antibody EIA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Testicular concentrations of Tf produced by Sertoli cells have been found to reflect Sertoli cell function [21]. The authors have found that the Tf concentration in canine testis becomes a clinical index of Sertoli cell function and spermatogenic function [10]. In the present study, there was no difference between the number of Sertoli cells before and after the operation.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Testicular concentrations of Tf produced by Sertoli cells have been found to reflect Sertoli cell function [21]. The authors have found that the Tf concentration in canine testis becomes a clinical index of Sertoli cell function and spermatogenic function [10]. In the present study, there was no difference between the number of Sertoli cells before and after the operation.…”
Section: Discussioncontrasting
confidence: 40%
“…Testicular Tf concentrations were determined by our microtiter plate double-antibody EIA method [10]. Briefly, Tf was purified from male dog serum by DEAE-Affi-Gel Blue chromatography and gel filtration.…”
Section: Animals and Surgerymentioning
confidence: 99%
“…The right testis and the left testis were biopsed under halothane inhalation anesthesia 1 week before and 5 weeks after the start of hormone treatment, respectively. The testicular tissue collected was divided into two portions, with one portion being used to measure testicular transferrin (Tf) concentrations by our EIA [6], and the other portion being used for histological examination after staining with PAShematoxylin. Germ cell counting was performed by the methods described previously [10] in 5 seminiferous tubules at stage 9 of the seminiferous epithelial cycle.…”
mentioning
confidence: 99%
“…This study focused on apoptotic cells in the testis of azoospermic dogs in relation to blood levels of luteinizing hormone (LH), T, and E 2 . The concentrations of testicular transferrin (Tf) were also measured as a marker of Sertoli cell function [12,16].…”
mentioning
confidence: 99%
“…The biopsied testicular tissues were examined for Tf concentrations by enzyme immunoassay [12]. All the data were statistically analyzed by Student's t-test.…”
mentioning
confidence: 99%